Решите уравнение: [latex]5*4^{x^2+4x} + 20*10^{x^2+4x-1} - 7*25^{x^2+4x} = 0[/latex]
Решите уравнение:
[latex]5*4^{x^2+4x} + 20*10^{x^2+4x-1} - 7*25^{x^2+4x} = 0[/latex]
Ответ(ы) на вопрос:
1) [latex]20*10^{x^2+4x-1}=20*10^{x^2+4x}:10=2*10^{x^2+4x}[/latex]
2) Делим все на [latex]25^{x^2+4x}[/latex]
Получаем
[latex]5*( \frac{4}{25} )^{x^2+4x}+ 2*( \frac{10}{25} )^{x^2+4x}-7=0 [/latex]
[latex]5*(( \frac{2}{5} )^{x^2+4x})^2+2*( \frac{2}{5} )^{x^2+4x}-7=0[/latex]
Замена
[latex]( \frac{2}{5} )^{x^2+4x}=y[/latex]
Заметим, что y > 0 при любом x.
5y^2 + 2y - 7 = 0
(y - 1)(5y + 7) = 0
[latex]y1=( \frac{2}{5} )^{x^2+4x}=1=( \frac{2}{5} )^0[/latex]
[latex]x^2+4x=0[/latex]
x1 = 0; x2 = -4
[latex]y2=( \frac{2}{5} )^{x^2+4x}=-7/5\ \textless \ 0[/latex]
Решений нет.
Ответ: x1 = 0; x2 = -4
Не нашли ответ?
Похожие вопросы